AB1132 Development of Quality Criteria for the Assessment of Care in Rheumatoid Arthritis. (9th June 2015) - Andreu, J.L.; Martín-Martínez, M.A.; Corominas, H.; Pérez-Venegas, J.J.; Román-Ivorra, J.A.; Sánchez-Alonso, F.; Alperi, M.; Blanco, R.; Caliz, R.; Chamizo, E.; Graña, G.; Hernández-Cruz, B.; et al.
Abstract : Background: The Treat to Target strategy (T2T) for RA includes an early diagnosis and start of Disease Modifying Antirheumatic Drugs (DMARDs) targeted to achieve remission (or low inflammatory activity) defined by composite measures, and periodic adjustment of treatment in order to reach pre-defined goals. Objectives: The aim of our work was to develop a tool to evaluate the quality of care in patients with RA according to the T2T strategy. Methods: Firstly, the scientific committee of the project proposed a series of quality criteria about different aspects of RA managing, like time to diagnosis and to starting the first DMARD, establishment of therapeutic targets, therapy intensification according to a pre-defined target, optimal use of methotrexate, evaluation of comorbidities and the use of safety measures before biological therapy. In a second phase, this set of criteria was submitted for evaluation by a group of 20 experts who, in two Delphi rounds, scored the relevance of the criteria and the feasibility of being obtained by retrospective evaluation of clinical records. Those criteria with a median score ≥7.5 in the Delphi rounds, both for relevance and feasibility, an IQ range ≤2.5, and a degree of agreement (score ≥8) ≥80%, were selected. Results: Initially, 37 quality criteria were proposed. They were submitted to a first Delphi round. Twelve of them needed a second round, since they did not reach consensus initially. After the analysis of the second round, a consensus was reached for 31 criteria. Some of these criteria were: a period <2 weeks between the first visit to the rheumatologist and the RA diagnosis; a period <2 weeks from the first consultation to the beginning of the first DMARD; to consider criteria of poor prognosis to decide the therapy; advice of quitting smoking and reaching ideal body weight; evaluation of disease activity by indexes like the 28 joints-Disease Activity Score (DAS28) or Simple Disease Activity Index (SDAI); clinical evaluations every 4 weeks until reaching the target; therapeutic intensification according to a pre-defined target; ordering chest X-ray and tuberculosis tests before starting biological therapy; recording cardiovascular risk factors; advice about vaccination for flu and pneumococcus; or taking into account comorbidities in the decision of therapy. Conclusions: We have developed a set of criteria for the assessment of quality in the clinical management of RA, according to the T2T strategy. Disclosure of Interest: None declared